2012
DOI: 10.1159/000338382
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Untreated Dental Caries in Older Independently Living South Brazilians

Abstract: Background: The importance of psychological reactions in modifying oral health behaviors and salivary immunity has been shown previously, but few studies assessed whether psychological reactions are associated with caries in populations. Thus, the aim of this study was to examine the association of depressive symptoms with untreated caries using a hierarchal approach. Methods: In this cross-sectional study, a random sample of 390 South Brazilians aged 60 years or more was evaluated using a structured questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 84 publications
(54 reference statements)
0
26
0
4
Order By: Relevance
“…Depression's relationship with physical well‐being may be associated with some of its symptoms, namely lack of motivation and energy, causing functional limitation . Depression has also been shown to affect oral health measures . Thus, controlling for this variable in the models was an absolute need.…”
Section: Discussionmentioning
confidence: 99%
“…Depression's relationship with physical well‐being may be associated with some of its symptoms, namely lack of motivation and energy, causing functional limitation . Depression has also been shown to affect oral health measures . Thus, controlling for this variable in the models was an absolute need.…”
Section: Discussionmentioning
confidence: 99%
“…Stress and depressive symptoms are predictors of dental caries 5 and are associated with periodontal problems 6 . Stress and depressive symptoms are predictors of dental caries 5 and are associated with periodontal problems 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence, few studies have investigated the association between caries and depressive symptoms. In a study on the prevalence of depressive symptoms in an elderly population, Hugo et al (25) found an association between depressive symptoms and coronal caries.…”
Section: Discussionmentioning
confidence: 99%